2019
DOI: 10.1186/s13613-019-0611-y
|View full text |Cite
|
Sign up to set email alerts
|

Low-pressure support vs automatic tube compensation during spontaneous breathing trial for weaning

Abstract: BackgroundDuring spontaneous breathing trial, low-pressure support is thought to compensate for endotracheal tube resistance, but it actually should provide overassistance. Automatic tube compensation is an option available in the ventilator to compensate for flow-resistance of endotracheal tube. Its effects on patient effort have been poorly investigated. We aimed to compare the effects of low-pressure support and automatic tube compensation during spontaneous breathing trial on breathing power and lung venti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 33 publications
0
11
0
4
Order By: Relevance
“…The definition of weaning-induced pulmonary oedema used in this study could also explain the high prevalence, as we opted to standardize classification of patients based on objective criteria (echocardiography and/or biomarkers) rather than classify patients based on expert consensus [ 1 , 2 ], which may be subject to bias. We also used a challenging weaning trial that is likely to have markedly influenced the intrathoracic pressure [ 29 ]. In addition, it is likely that the early spontaneous breathing trial strategy relying on the presence of “readiness-to-wean criteria” rather on “readiness to extubate criteria” is partially responsible of the high prevalence of weaning-induced pulmonary oedema observed in our population.…”
Section: Discussionmentioning
confidence: 99%
“…The definition of weaning-induced pulmonary oedema used in this study could also explain the high prevalence, as we opted to standardize classification of patients based on objective criteria (echocardiography and/or biomarkers) rather than classify patients based on expert consensus [ 1 , 2 ], which may be subject to bias. We also used a challenging weaning trial that is likely to have markedly influenced the intrathoracic pressure [ 29 ]. In addition, it is likely that the early spontaneous breathing trial strategy relying on the presence of “readiness-to-wean criteria” rather on “readiness to extubate criteria” is partially responsible of the high prevalence of weaning-induced pulmonary oedema observed in our population.…”
Section: Discussionmentioning
confidence: 99%
“…We set linear compliance and resistance as equal during inspiration and expiration. At the patient effort step of the ASL 5000 script, we used the analog output of the esophageal pressure tracing in a representative subject included in the previously mentioned study comparing pressure support ventilation to ATC 3 (see the supplementary materials at http://www. rcjournal.com).…”
Section: Set Upmentioning
confidence: 99%
“…We recently reported 3 that breathing power was significantly higher with ATC than with low pressure support ventilation mode, both including a low PEEP, indicating that low pressure support ventilation provides pressure assistance beyond the pressure drop across ETT compensation. 4 Nevertheless, our previous work 3 used one brand of ventilator (Evita XL, Dräger, Germany) with all subjects, and the results may be different from those obtained with other ICU ventilators given that the algorithms governing ATC may differ. To explore this question further, we first performed an international survey to determine the rate of use ATC in daily practice.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The wide range of respiratory support, from automatic tube compensation to pressure support up to 10 cm H 2 O, generates a heterogeneous response that makes predicting the outcome difficult, leading to important clinical consequences. [6][7][8] The results of a study showed that 1-hour reconnection to mechanical ventilation after a tolerated SBT significantly reduced the reintubation rate in a population of patients who underwent SBT mostly by T-tube. 5 This result suggests that highly demanding SBT can contribute to extubation failure.…”
mentioning
confidence: 99%